The UWI-CARICOM partnership : still fundamental to on-going regional integration - Ventour, Jessie-May (2013)
Seeks the views of Caribbean leaders on how the University of the West Indies can partner more meaningfully with the CARICOM to help solve the many issues facing its peoples.